In acute promyelocytic leukemia (APL) low BAALC gene expression identifies a patient group with favorable overall survival and improved relapse free survival - Nolte, Florian; Hecht, Anna; Reinwald, Mark; Nowak, Daniel; Nowak, Verena; Hanfstein, Benjamin; Hofmann, Wolf-Karsten; Lengfelder, Eva (Leukemia research, 2013)
We evaluated the prognostic value of BAALC expression in 86 patients with acute promyelocytic leukemia (APL). At 10 years, the overall survival (OS) was 66% in all patients and 75% in patients who achieved a complete remission (CR). Patients in the BAALClow group showed an OS of 87% as compared to 60% in the BAALChigh group (p=0.019). This difference was more pronounced in treatment responders (92% vs. 70%; p=0.035). In multivariate analyses low BAALC expression retained its prognostic relevance. In conclusion, BAALC expression analysis might be useful in further risk stratification in APL patients.